APPROACH IS THE MAIN STRATEGIC DIRECTION THAT DEFINES THE COMPONENTS OF LEARNING THE UZBEK LANGUAGE - Yuldasheva, Dilnoza; Amirova, Shahzoda (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY RESEARCH AND INNOVATIVE TECHNOLOGIES, 2021)
Each stage in the development of language teaching methods characterizes its own approach. It is sometimes called a method in linguodidactics. The approach is the main strategic direction that determines all the components of the learning system: its goals, objectives and content, ways and means of achieving them, the activities of the teacher and the student, learning technologies (techniques), criteria for the effectiveness of the educational process, the control system.